An Economic Feasibility Study on Solar Installation for University Campus: A Case of Universiti Utara Malaysia - Shafie, S. M.; Hassan, M. G.; Sharif, K. I. M.; Nu’man, A. N.; Yusuf, N.N.A.N. (International Journal of Energy Economics and Policy, 2022)
Transforming towards renewable energy consumption has become the main agenda for the country due to the drawback of consuming conventional resources. Climate change, energy security, and price fluctuation are the main factors contributing towards the penetration of renewable energy. Solar energy seems to be the most attractive due to unlimited source of energy, and fundamentally, its availability will never run out. This form of energy can also be used as an alternative in producing electricity. Malaysia has potential in developing solar energy for daily usage due to its location in the equatorial area and acquiring approximately 400–600 MJ/ m–2 of solar radiation every month. Universiti Utara Malaysia (UUM) is a public higher learning institution located in Sintok, Kedah. Sintok is a potential area for the installation of this solar system because the area has a longer peak sun hour rate than other areas. The aims of this study are: (1) to analyse the factors involved in solar installation, and (2) to examine the economic feasibility of solar installation at a university campus. This study used a qualitative approach, whereby the data were taken from interviews with the Development and Maintenance Department of UUM and Detrolic Solar Company. The solar implementation in UUM could reduce the cost of energy usage annually. Furthermore, UUM could gain revenue from the Net Energy Metering (NEM) 3.0 Government Ministries and Entities (GoMEn) incentive. Solar installation in the campus could hasten the effort of UUM moving towards a green and eco-friendly university campus. It is best believed that this effort could be a success if UUM is ready to move towards sustainable energy with solar consumption.